Розвиток партнерських відносин підприємств з вищими навчальними закладами - Щербата, Тетяна Сергіївна (Національний університет "Львівська політехніка", 2017)
Дисертацію присвячено вирішенню наукового і прикладного завдання розвитку партнерських відносин підприємств з вищими начальними закладами. Набула подальшого розвитку класифікація видів партнерських відносин підприємств з вищими навчальними закладами, а також удосконалено послідовність вибору стратегії розвитку партнерських відносин ІТ-підприємств з ВНЗ на основі матриці «індивідуальна цінність – функціональна цінність». У роботі розвинуто модель вибору ВНЗ як потенційного партнера ІТ-підприємства, що базується на виокремленні аутсорсингового, продуктового та змішаного виду підприємства та розподілі критеріїв оцінювання ВНЗ як партнера підприємства. Розроблено класифікацію бізнес-процесів аутсорсингового, продуктового та змішаного виду ІТ-підприємства. Удосконалено модель визначення рівня цінності партнерських відносин ІТ-підприємства з ВНЗ на засадах виокремлення низки критеріїв оцінювання індивідуальної та функціональної складових. Диссертация посвящена решению научного и прикладного задания развития партнерских отношений предприятий с высшими учебными заведениями. Приобрела дальнейшего развития классификация видов партнерских отношений предприятий с высшими учебными заведениями, а также усовершенствована последовательность выбора стратегии развития партнерских отношений ИТ-предприятий с высшими учебными заведениями. Развита модель выбора ВУЗа как потенциального партнера ИТ-предприятия, которая базируется на выделении аутсорсингового, продуктового и смешанного вида предприятия и распределении критериев оценивания высших учебных заведений. Разработана классификация бизнес-процессов аутсорсингового, продуктового и смешанного вида ИТ-предприятия. Усовершенствована модель определения уровня ценности партнерских отношений ИТ-предприятия с высшими учебными заведениями на основе выделения ряда критериев оценки индивидуальной и функциональной составляющих. The dissertation provides a scientific and practical solution of tasks that concern development of partnership relations of enterprises with institutions of higher education. The scientific references study results in the field of enterprise partnership research confirmed the importance of individual approach in considering a partnership with higher education institution. Implying the analysis principled allowed considering the relation between enterprise and higher education institution as an opened system. Performed research has shown that main partnership features between enterprise and higher education institution are interactivity, limitations in decision making, synergistic effect from the obtained result, unification in a certain system of values and environment, interest in investment and innovative activities, flexibility and adaptability. The information and communication technology evolution, globalization processes, education transformation and knowledge-based-economy have led to a powerful growth of partnership relations between industry and university worldwide. The potential of such cooperation is huge: local arrangements can lead the growth of regional economy development. There is an enormous economic literature estimating the impact of UBC on society. Considered foreign experience of partnership development between enterprise and higher education institution allowed to make the following conclusions: bureaucracy at higher education institution causes negative influence on partnership development; higher education institution, which are engaged in applied research have higher grade on partnership development; trust and competence contribute to partnership development; the cooperation level between enterprise and technical higher education institutions is higher, rather than with natural-profiled higher education institutions. In order to coordinate the UBC development in Ukraine, the special events, forums, and programs were created. The TEMPUS Project "National Education Framework for Enhancing IT Students’ Innovation and Entrepreneurship" and Horizon2020 united a lot of national and EU universities. The tasks of such programs are: to increase scientific and practical recommendations to the UBC development. The experience of EU countries shows that the UBC has a powerful impact on different target groups: students, academics, universities, business, society, economics. Unfortunately, the level of such cooperation in Ukraine is low and needs development and government reforms. On the basis of poll materials analysis of IT enterprises cooperating with higher education institutions during one to five years (82%), there are reasons to assert, that main barriers in cooperation development are: high bureaucracy level, lack of higher education institution’s financial independency, much time required to make changes in academic programs. The research showed the main forms of cooperation between enterprise and higher education institution, which are: practice for students at the enterprise; conducting of courses, educational lectures at higher educational institutions; support of student competitions, olympiads; development of educational programs in cooperation with higher education institutions; creation of educational laboratories; development of joint scientific research. On the basis of the results of separating forms of cooperation, it is possible to conclude that the most popular ways of cooperation are conducting practicum for students and providing courses, educational lectures in universities. Performed research has showed, that there are positive tendencies in cooperation development between IT enterprises and higher education institutions, which are: the education modernization standard is developed, which is based on cooperation development between IT enterprises and higher education institutions; the process of active involvement of Ukrainian higher education institutions in international projects of youth entrepreneurship in IT is engaged; the mechanism of spreading the join-projects practice between higher education institutions and IT enterprises across the educational process is formed. The developed model of choosing university as a potential partner of the IT enterprise is based on a number of factors of partner interaction: the goals of the partnership development with universities; setting up tasks of partnership with universities with specialization for product, outsourcing and mixed types; selection of specialized universities (segmentation); determining the system of assessment indicators of universities and determining their importance by experts. In dissertation work it is offered to conduct evaluation of the value of partnership relations in two stages: individual and functional. The first stage of the assessment includes the following indicators: stability, loyalty, safety, fulfillment and flexibility of the partner. The second stage of the evaluation includes the indicators of the diagnostics of the system of partnership: the management distance, the level of the tasks achievement, the quality of the communication environment, adaptability of the system, coordination of actions of the participants within the system. The result of the evaluation of the indicator may be: "very low", "low", "average", "high" and "very high". The improved procedure for choosing a strategy for the development of partnership relations between the IT enterprise and the higher education institution, taking into account the integral indicator of the value of partnership relations and the density of the relationship between the IT enterprise and the institution of higher education is shown in the work. This order consists of 7 steps: the formation of a working group at the enterprise; determination of goals and tasks of the development of partnerships with universities; gathering information on the state of affairs; carrying out of the evaluation and calculation of the integral indicator of the value of the partner relations of the IT enterprise with the university; determination of the relationship between the IT enterprise and the institution of higher education; choice of strategy on the matrix "individual value of partnership – functional value of partnership". Although Ukraine is taking steps for improving UBC, but they are still far from ideal. However, a partnership between university and business is a great challenge that is necessary to accept. The key opportunities for startups in providing cooperation with university in IT cluster are: shortening of the product development time; lowering of the product development price; high quality of products; concentrate operation management. The good practices of students’ startups support and cooperation HEIs with industry will increase the general political, market, economic, scientific development.
Развитие партнерських отношений предприятий с высшими учебными заведениями
Development of partnership relations of enterprises with institutions of higher education
Keywords: партнерські відносини підприємства; вищий навчальний заклад; інформаційно-технологічні (ІТ) підприємства; навчальний процес; партнерские отношения предприятия; высшее учебное заведение; информационно-технологические (ИТ) предприятия; учебный процесс; partnership relations; institution of higher education; information technology enterprises; education process